The role of geriatricians in hospital palliative care units for elderly patients affected by end stage diseases. (2nd May 2022) - Sganga, Federica; Salerno, Andrea; Frizza, Alessandro; Turriziani, Adriana; Barillaroa, Christian; Bernabei, Roberto
Abstract : Objective: To show the importance of geriatricians in the assessment and treatment of patients with terminal illnesses requiring palliative care. Methods: This was a retrospective epidemiological study, in which the authors used data relating to 229 patients with terminal stage cancer/advanced chronic diseases, which were evaluated by a palliative care team and collected from January to December 2018. Results: The average age of the sample was 72 years. The sample was divided into two groups, called 'advanced cancer' (N=161, 70.3%) and 'advanced chronic diseases' (N=68, 29.6%). The authors found that patients with advanced chronic diseases had the highest age, highest number of comorbidities and higher indicators of complex care. The authors also showed that, in advanced chronic diseases, the factors that are associated with increased hospital death are: bedridden (OR=3, 778; 95% CI=1, 371-10, 409), dysphagia (OR=2, 038; 95% CI=1, 005-4, 133) and a higher number of diseases (OR=1, 446; 95% CI=1, 179–1, 774). Discussion: Given these findings, there is a high prevalence of elderly hospitalised patients with advanced chronic end-stage disease, a classic geriatric condition, who need access to palliative care services. Conclusion: The authors believe that an increase in geriatricians dedicated to palliative care services is needed to ensure that these patients have equal access to continuity of care services and optimal treatment.